48.3k views
0 votes
Helppppp pleaseeeeee

Helppppp pleaseeeeee-example-1
User Mark Meeus
by
5.9k points

2 Answers

6 votes
Let y = x^2 - 16
x^2 = y + 16
x = +/- sqrt ( y + 16)

f-1(x) = +/- sqrt (x + 16) Its the second choice.
User TechnicalViking
by
5.5k points
4 votes
For this case we have the following function:
f (x) = x ^ 2 - 16
Rewriting the function we have:

y = x ^ 2 - 16
From here, we clear the value of x.
We have then:

x ^ 2 = y + 16

x = +/- √(y+16)
Then, we return the change of variables.
We have then:

y = +/- √(x+16)
Rewriting, we have the inverse function is:

f(x)^(-1)=+/- √(x+16)
Answer:
the inverse function is:

f(x)^(-1)=+/- √(x+16)
option 2
User Sunnyrjuneja
by
5.8k points